2022
DOI: 10.32890/jps2022.25.10
|View full text |Cite
|
Sign up to set email alerts
|

Tingkah Laku Mencederakan Diri Sendiri Dalam Kalangan Remaja

Abstract: Makalah ini membincangkan mengenai fenomena tingkah laku remaja mencederakan diri sendiri. Kes tingkah laku remaja mencederakan diri sendiri ini sememangnya wujud, dan jumlahnya semakin meningkat setiap tahun seiring laporan masalah kesihatan mental dalam kalangan kanak-kanan dan remaja yang dikeluarkan oleh Kementerian Kesihatan Malaysia melalui laporan Statistik Tinjauan Kesihatan dan Morbiditi Kebangsaan. Fenomena ini perlu diberikan perhatian sewajarnya oleh semua pihak terutamanya guru bimbingan dan kauns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The FACES II was used in two studies. Although one study reported a Cronbach's alpha of 0.82 for the full scale (Ghani, 2013), another study did not report any psychometric properties. Among the three versions, the FACES III is the most popular scale in studies conducted on Malaysian samples, where 11 studies adopted it to measure FF.…”
Section: Resultsmentioning
confidence: 99%
“…The FACES II was used in two studies. Although one study reported a Cronbach's alpha of 0.82 for the full scale (Ghani, 2013), another study did not report any psychometric properties. Among the three versions, the FACES III is the most popular scale in studies conducted on Malaysian samples, where 11 studies adopted it to measure FF.…”
Section: Resultsmentioning
confidence: 99%
“…In Malaysia, several studies have also confirmed the presence of NSSI behavior in the local context, particularly among non-clinical samples (Johari et al, 2022;Masiran et al, 2017). Furthermore, the rate of NSSI behavior among adults is 19 per 100,000, and the rate of NSSI behavior among children and adolescents is 12 per 100,000 in Malaysia (Masiran et al, 2017).…”
Section: Introductionmentioning
confidence: 92%
“…Mental health is considered the most important element in human life (Johari et al, 2022). According to the World Health Organization (2019), mental health refers to a state of wellbeing in which each individual realizes their potential, can cope with life's pressures, work productively, and contribute to society.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations